PENGARUH METODE LATIHAN CIRCUIT TRAINING TERHADAP KEKUATAN MAKSIMAL PADA ATLET DAYUNG KABUPATEN INDRAMAYU - Yoga Firdaus, - (2020)
The absence of diversity of exercises for novice athletes in the sport causes saturation when running exercises. To overcome saturation during exercise, it takes a variety of exercises while increasing maximum strength . This study aims to test the significant influence of circuit training methods on maximum strength. This research method uses experimental One Group Pre-test Post-test design and saturated sampling. Samples used as many as 10 people. The instrument used in this study was 1 RM test. With the start of the pre-test at the beginning, conduct circuit training exercises for 16 meetings and post-test at the end. Data retrieval with data analysis method done by using paired t test samples to get data results from pre-test and post-test that have been done. The result of pre-test is each test item is bench press 0.238 > 0.05, squat 0.041 < 0.05, bench row 0.109 > 0.05, deadlift 0.243 > 0.05, and post-test each test item i.e. bench press 0.270 > 0.05, squat 0.093 > 0.05, bench row 0.822 > 0.05, deadlift 0.602 > 0.05. Based on the hypothesis testing using the Wilcoxon Signed Ranks Test, it shows that the pre-test and post-test bench press results are 0.004 <0.05, the pre-test results and the post-test squat results are 0.004 <0.05, the results The pre-test and post-test bench row results are 0.005 <0.05, the pre-test and post-test deadlift results are 0.005 <0.05, it is concluded that H0 is rejected and H1 is accepted. It can be concluded that this circuit training method has a significant influence on maximum strength.